Characterization of vaginal microbiota across female reproductive phases - Zhai, Qingzhi; Gao, Yuan; Wang, Mingyang; Li, Li; Li, Lian; Li, Jianghua; Ma, Ying; Niu, Ke; Ye, Mingxia (Frontiers in Microbiology, 2025)
BackgroundThe vaginal microbiota plays a crucial role in women’s reproductive health, but its composition and function throughout different female reproductive phases remain poorly understood. This study aimed to investigate the dynamic variations in vaginal microbial communities corresponding to different hormonal states throughout the female reproductive phase.MethodsVaginal samples were collected from 150 healthy women across five reproductive phases: follicular phase, luteal phase, early pregnancy, lactation, and menopause (30 samples per group). 16S rRNA sequencing was used to analyze the microbial composition. Alpha and beta diversity analyses were performed, and random forest models were constructed to identify key microbial taxa associated with each phase. Functional profiling was conducted using Clusters of Orthologous Groups of Proteins (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases.ResultsMicrobial communities show significant variations across the different reproductive phases. Firmicutes dominate in the early reproductive phases but decrease notably during lactation and menopause. Conversely, Bacteroidetes, Actinobacteria, and Proteobacteria increase in later phases. At the genus level, Lactobacillus maintains a higher abundance during reproductive phases but declines during lactation and menopause. Peak microbial diversity occurs during lactation. Functional predictions reveal distinct phase-specific microbial functions. The follicular phase is enriched in pathways associated with nitrotoluene degradation and flavonoid biosynthesis, potentially reflecting estrogen-mediated regulation. Lactation shows enrichment in pathways related to protein digestion and fatty acid metabolism, consistent with increased nutritional demands. Menopause is characterized by enrichment in steroid hormone biosynthesis pathways. In early pregnancy, enrichment of functions related to the adenine nucleotide translocator and phosphate carrier reversible complex suggests functional adaptation of the microbiota to early gestational physiology.ConclusionOur study reveals dynamic variations in vaginal microbiota across reproductive phases, closely linked to hormonal states, and highlights potential microbial targets for enhancing women’s reproductive health.